Early Grade Reading Rainbow : A Quick Guide to Ending Learning Poverty - World Bank (Washington, DC, 2022)
The Early Grade Reading Rainbow is a simple way to understand the key messages from the science of reading. Each rainbow color represents one of eight key skills students need to master to become independent readers. This guide presents the basic elements of an approach to decreasing learning poverty through planning for a program of reading instruction aligned with the science of reading. Each page deals with a single element of the program: it starts with understanding the key findings of the science of reading and then proposes how these can be instantiated in a multi-year series composed of daily lesson plans, each building on the previous one. It also proposes that teacher guidance and support be provided, and that instruction and materials be in the language students best speak and understand. It further proposes that teaching and learning materials be made available to each child, that assessments be aligned with the progression of subskills that are the focus of instruction, and that these materials be adapted to the local linguistic and cultural context.